Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Biến đổi \(\frac{x}{y^3-1}-\frac{y}{x^3-1}=\frac{x^4-x-y^4+y}{\left(y^3-1\right)\left(x^3-1\right)}=\frac{\left(x^4-y^4\right)-\left(x-y\right)}{xy\left(y^2+y+1\right)\left(x^2+x+1\right)}\)
(Do x+y=1 => \(\hept{\begin{cases}y-1=-x\\x-1=-y\end{cases}}\))
\(=\frac{\left(x-y\right)\left(x+y\right)\left(x^2+y^2\right)-\left(x-y\right)}{xy\left(x^2y^2+y^2x+y^2+yx^2+xy+y+x^2+x+1\right)}\)
\(=\frac{\left(x-y\right)\left(x^3+y^3-1\right)}{xy\left[x^2y^2+xy\left(x+y\right)+x^2+y^2+xy+2\right]}\)
\(=\frac{\left(x-y\right)\left(x^2-x+y^2-y\right)}{xy\left[x^2y^2+\left(x+y\right)^2+2\right]}=\frac{\left(x-y\right)\left[x\left(x-1\right)+y\left(y-1\right)\right]}{xy\left(x^2y^2+3\right)}\)
\(=\frac{\left(x-y\right)\left[x\left(-y\right)+y\left(-x\right)\right]}{xy\left(x^2y^2+3\right)}=\frac{\left(x-y\right)\left(-2xy\right)}{xy\left(x^2y^2+3\right)}=\frac{-2\left(x-y\right)}{x^2y^2+3}\)
\(\Rightarrow\frac{x}{y^3-1}-\frac{y}{x^3-1}+\frac{2\left(x-y\right)}{x^2y^2+3}=0\left(đpcm\right)\)
\(\frac{x}{y^3-1}-\frac{y}{x^3-1}\)
\(=\frac{1-y}{\left(y-1\right)\left(y^2+y+1\right)}-\frac{1-x}{\left(x-1\right)\left(x^2+x+1\right)}\)
\(=\frac{-1}{y^2+y+1}+\frac{1}{x^2+x+1}\)
\(=\frac{-x^2-x-1+y^2+y+1}{\left(x^2+x+1\right)\left(y^2+y+1\right)}\)
\(=\frac{\left(y^2-x^2\right)+y-x}{x^2y^2+x^2y+x^2+xy^2+xy+x+y^2+y+1}\)
\(=\frac{\left(y-x\right)\left(y+x\right)+y-x}{x^2y^2+x^2y+xy^2+x^2+xy+y^2+x+y+1}\)
\(=\frac{y-x+y-x}{x^2y^2+xy\left(x+y\right)+x\left(x+y\right)+y^2+x+y+1}\)
\(=\frac{2\left(y-x\right)}{x^2y^2+xy+x+y^2+x+y+1}\)
\(=\frac{2\left(y-x\right)}{x^2y^2+x\left(y+1\right)+y^2+x+y+1}\)
\(=\frac{2\left(y-x\right)}{x^2y^2+\left(1-y\right)\left(y+1\right)+y^2+\left(x+y\right)+1}\)
\(=\frac{2\left(y-x\right)}{x^2y^2+1-y^2+y^2+1+1}\)
\(=\frac{2\left(y-x\right)}{x^2y^2+3}\)
ĐK: \(x;y;z\ne0\)
\(\frac{y+z}{x}+\frac{x+z}{y}+\frac{x+y}{z}+3=\left(\frac{y+z}{x}+1\right)+\left(\frac{x+z}{y}+1\right)+\left(\frac{x+y}{z}+1\right)-3+3\)
\(=\left(x+y+z\right)\left(\frac{1}{x}+\frac{1}{y}+\frac{1}{z}\right)=0\left(đpcm\right)\)
Xét \(\frac{x}{y^3-1}+\frac{y}{x^3-1}=\frac{1-y}{y^3-1}+\frac{1-x}{x^3-1}=-\frac{1}{x^2+x+1}-\frac{1}{y^2+y+1}\)
\(=-\frac{x^2+y^2+x+y+2}{\left(x^2+x+1\right)\left(y^2+y+1\right)}=-\frac{x^2+y^2+3}{x^2y^2+xy\left(x+y\right)+x^2+y^2+xy+x+y+1}\)
\(=-\frac{\left(x+y\right)^2-2xy+3}{x^2y^2+x^2+y^2+2xy+2}=-\frac{4-2xy}{x^2y^2+3}=\frac{2\left(xy-2\right)}{x^2y^2+3}\)
từ đó ta có đpcm
1/
\(x^2-xy-2y^2=0\Leftrightarrow x^2+xy-2xy-2y^2=0\)
\(\Leftrightarrow x\left(x+y\right)-2y\left(x+y\right)=0\)
\(\Leftrightarrow\left(x+y\right)\left(x-2y\right)=0\Rightarrow x=2y\) (do \(x+y\ne0\))
\(\Rightarrow P=\frac{2y-y}{2y+y}=\frac{y}{3y}=\frac{1}{3}\)
2/
\(x^4-30x^2+31x-30=0\)
\(\Leftrightarrow x^4+x-30x^2+30x-30=0\)
\(\Leftrightarrow x\left(x^3+1\right)-30\left(x^2-x+1\right)=0\)
\(\Leftrightarrow x\left(x+1\right)\left(x^2-x+1\right)-30\left(x^2-x+1\right)=0\)
\(\Leftrightarrow\left(x^2+x-30\right)\left(x^2-x+1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x^2+x-30=0\\x^2-x+1=0\end{matrix}\right.\) \(\Leftrightarrow\left[{}\begin{matrix}\left(x-5\right)\left(x+6\right)=0\\\left(x-\frac{1}{2}\right)^2+\frac{3}{4}=0\left(vn\right)\end{matrix}\right.\) \(\Rightarrow\left[{}\begin{matrix}x=5\\x=-6\end{matrix}\right.\)
\(x+y=1\Rightarrow\left\{{}\begin{matrix}y-1=-x\\x-1=-y\end{matrix}\right.\) \(\Rightarrow\left\{{}\begin{matrix}\left(y-1\right)^2=x^2\\\left(x-1\right)^2=y^2\end{matrix}\right.\)
\(\frac{x}{y^3-1}-\frac{y}{x^3-1}+\frac{2\left(x-y\right)}{\left(xy\right)^2+3}=\frac{x}{\left(y-1\right)\left(y^2+y+1\right)}-\frac{y}{\left(x-1\right)\left(x^2+x+1\right)}+\frac{2\left(x-y\right)}{\left(xy\right)^2+3}\)
\(=\frac{-1}{y^2+y+1}+\frac{1}{x^2+x+1}+\frac{2\left(x-y\right)}{\left(xy\right)^2+3}=\frac{-1}{x^2+3y}+\frac{1}{y^2+3x}+\frac{2\left(x-y\right)}{\left(xy\right)^2+3}\)
\(=\frac{-y^2-3x+x^2+3y}{\left(xy\right)^2+3x^3+3y^3+9xy}+\frac{2\left(x-y\right)}{\left(xy\right)^2+3}=\frac{\left(x-y\right)\left(x+y\right)-3x+3y}{\left(xy\right)^2+3\left(x+y\right)\left(\left(x+y\right)^2-3xy\right)+9xy}+\frac{2\left(x-y\right)}{\left(xy\right)^2+3}\)
\(=\frac{-2\left(x-y\right)}{\left(xy\right)^2+3}+\frac{2\left(x-y\right)}{\left(xy\right)^2+3}=0\)
\(x+y=1\)\(\Leftrightarrow\hept{\begin{cases}x-1=-y\\y-1=-x\end{cases}}\)
Ta có: \(\frac{x}{y^3-1}-\frac{y}{x^3-1}=\frac{x}{\left(y-1\right)^3+3y\left(y-1\right)}-\frac{y}{\left(x-1\right)^3+3x\left(x-1\right)}\)
\(=\frac{x}{-x^3-3xy}-\frac{y}{-y^3-3xy}=\frac{x}{-x\left(x^2+3y\right)}-\frac{y}{-y\left(y^2+3x\right)}\)
\(=\frac{-1}{x^2+3y}+\frac{1}{y^2+3x}=\frac{-\left(y^2+3x\right)+\left(x^2+3y\right)}{\left(x^2+3y\right)\left(y^2+3x\right)}=\frac{-y^2-3x+x^2+3y}{x^2y^2+3x^3+3y^3+9xy}\)
\(=\frac{\left(x^2-y^2\right)-3\left(x-y\right)}{x^2y^2+3\left(x^3+y^3\right)+9xy}=\frac{\left(x-y\right)\left(x+y\right)-3\left(x-y\right)}{x^2y^2+3\left[\left(x+y\right)^3-3xy\left(x+y\right)\right]+9xy}\)
\(=\frac{\left(x-y\right)-3\left(x-y\right)}{x^2y^2+3\left(1-3xy\right)+9xy}=\frac{-2\left(x-y\right)}{x^2y^2+3-9xy+9xy}=\frac{-2\left(x-y\right)}{x^2y^2+3}\)
\(\Rightarrow\frac{x}{y^3-1}-\frac{y}{x^3-1}+\frac{2\left(x-y\right)}{x^2y^2+3}=\frac{-2\left(x-y\right)}{x^2y^2+3}+\frac{2\left(x-y\right)}{x^2y^2+3}=0\)( đpcm )